Assessing Employee Performance in the Information Technology Department Using K-Means Clustering: A Case Study Approach - Sakalessy, Afelia Jozalin Elisa; Purnomo, Hindriyanto Dwi (Universitas Bina Darma, 2024)
This research explores the utilization of the K-Means method for evaluating the performance of employees within the Information Technology Department at PT Nusa Halmahera Minerals. The research leverages data from Manage Engine to analyze diverse parameters of employee performance. By employing the K-Means method, employees are categorized based on specific characteristics, facilitating a deeper understanding of each individual's contribution and potential in attaining company objectives. The implementation of the K-Means method aims to offer a more objective perspective on employee performance, empowering companies to make informed decisions in the enhancement and development of their human resources.